2010
DOI: 10.1007/s11426-010-4105-x
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor protects neurons from GdCl3-induced impairment in neuron-astrocyte co-cultures

Abstract: Gadolinium (Gd 3+ ) complexes are important contrast agents in medical magnetic resonance imaging (MRI) and of great potential value in brain research. In order to better understand the mechanisms of the action of Gd 3+ on neurons in the complex central nervous system (CNS), the neurotoxic actions of GdCl 3 have been investigated in both neuron monoculture and astrocyteneuron co-culture systems. Measurements of lactate dehydrogenase release showed that GdCl 3 causes significant cell death of monocultured neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…Feng X. et al have reported a remarkable increase in LDH leakage, after exposure of rat cortical neuron cells to GdCl 3 (0.2, 2, 20 and 100 µM) even at low micromolar doses (41). Almost in the same time, Xia Q. et al (42) revealed that GdCl 3 (0.2, 2, and 20 µM) induced in neurons a decrease of cell viability and an increase of LDH released onto the culture medium in a time-and concentration-dependent manner (43). Our data are not in accordance with these two studies, due to the fact that in our experiments Gd 3+ was firstly complexed by DOTA or DOTP and secondly embedded in the nanogels.…”
Section: Discussionmentioning
confidence: 89%
“…Feng X. et al have reported a remarkable increase in LDH leakage, after exposure of rat cortical neuron cells to GdCl 3 (0.2, 2, 20 and 100 µM) even at low micromolar doses (41). Almost in the same time, Xia Q. et al (42) revealed that GdCl 3 (0.2, 2, and 20 µM) induced in neurons a decrease of cell viability and an increase of LDH released onto the culture medium in a time-and concentration-dependent manner (43). Our data are not in accordance with these two studies, due to the fact that in our experiments Gd 3+ was firstly complexed by DOTA or DOTP and secondly embedded in the nanogels.…”
Section: Discussionmentioning
confidence: 89%
“…ER stress and oxidative stress also have been reported playing vital role in heavy metal-induced neurotoxicity (Erikson et al 2004;Biagioli et al 2008). Our previous study has revealed that oxidative stress was involved in the neurotoxicity of Gadolinium (Feng et al , 2011Xia et al 2010). Meanwhile, in another related research, we reported that Gadolinium could trigger ER stress in primary cultured rat cortical astrocytes (Feng et al , 2011.…”
Section: Discussionmentioning
confidence: 91%
“…Our previous study has revealed that oxidative stress was involved in the neurotoxicity of Gadolinium (Feng et al. 2010, 2011; Xia et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Primary cortical neuronal cultures were prepared as described previously . Eighteen‐day‐old embryonic Sprague Dawley rats were sacrificed, and cortex tissues were obtained quickly.…”
Section: Methodsmentioning
confidence: 99%